Multisystemic eosinophilic epitheliotropic disease in a horse in Brazil - Cláudio João Mourão Laisse (Ciência Rural, 2017)
Equine multisystemic eosinophilic epitheliotropic disease (MEED) is a rare disease, characterized by eosinophilia and eosinophilic infiltration of several organs. A 5-year-old horse presented pruritus, areas of alopecia, and moderate eosinophilia. The horse was treated with corticosteroids and antibiotics without substantial improvement; and after the disease progressed to fever, diarrhea, gastric reflux and progressive weight loss. Due to poor prognosis the horse was euthanized. Necropsy revealed poor body condition, multiple to coalescing foci of alopecia, with epidermal ulcerations and crusts on the head and distal parts of the limbs. The proximal duodenum was enlarged, with 3 intraluminal nodules. Histopathological evaluation revealed eosinophilic granulomas in the skin, oral mucosa, duodenum, pancreas, and mesenteric lymph nodes, which were associated with infiltrates of eosinophils, lymphocytes, macrophages, multinucleated giant cells, and occasional plasma cells, along with fibrovascular connective tissue proliferation. MEED should be included in the differential diagnosis of horses with skin lesions concomitant with clinical signs of gastr ointestinal illness.